Improvement of reliability of heavy transport machines by the technological methods - Посвятенко, Е.К.; Кравченко, С.О.; Посвятенко, Н.І. (Eastern-European Journal of Enterprise Technologies, 2010)
Results of research of process of discrete hardening of pig-iron and steel details of type a cranked shaft of engines of heavy cars are presented. Influence of new technology through a complex of physicomechanical and operational characteristics on increase of a resource of the engine and the car as a whole is shown.